How do you simplify the expression (cos^2(x)+cos(x)-20)/(cos^2(x)-16)cos2(x)+cos(x)20cos2(x)16?

1 Answer
Apr 28, 2018

(cos^2x+cosx-20)/(cos^2x-16)=1+1/(cosx+4)cos2x+cosx20cos2x16=1+1cosx+4

Explanation:

(cos^2x+cosx-20)/(cos^2x-16)cos2x+cosx20cos2x16

= (cos^2x+5cosx-4cosx-20)/((cosx-4)(cosx+4))cos2x+5cosx4cosx20(cosx4)(cosx+4)

= (cosx(cosx+5)-4(cosx+5))/((cosx-4)(cosx+4))cosx(cosx+5)4(cosx+5)(cosx4)(cosx+4)

= ((cosx-4)(cosx+5))/((cosx-4)(cosx+4))(cosx4)(cosx+5)(cosx4)(cosx+4)

= (cosx+5)/(cosx+4)cosx+5cosx+4

= 1+1/(cosx+4)1+1cosx+4